2019
DOI: 10.1617/s11527-019-1393-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calcined illitic clays (brick clays) and low-grade kaolinitic clays as supplementary cementitious materials

Abstract: The use of calcined clays as supplementary cementitious materials (SCMs) has been identified as a viable option to decrease the CO 2 emissions related to cement production. However, while extensive data is available about kaolinitic clays in this context, other clays such as illitic clays appear to be under-studied. Therefore, in the present study, two illitic clays were compared to two low-grade kaolinitic clays in terms of transformations in the calcination temperature range 650-900°C, and performance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 25 publications
3
18
0
1
Order By: Relevance
“…Uchima et al obtained good results that showed pozzolanic activity in biomass and kaolinitic clay [17]. The present study could suggest that illite and kaolinite could have a synergic effect because a study carried out by Msinjili et al that compared illite and kaolinite clays as supplementary cementitious materials concluded that all of these kinds of materials have pozzolanic activity but differ in the temperature at which they activate [18]. It is important to note that in this study, it was possible that the illite had a disordered structure-a normal characteristic of this mineral [19]-and so activated with kaolinite in the same temperature range.…”
Section: Characterizationmentioning
confidence: 48%
See 1 more Smart Citation
“…Uchima et al obtained good results that showed pozzolanic activity in biomass and kaolinitic clay [17]. The present study could suggest that illite and kaolinite could have a synergic effect because a study carried out by Msinjili et al that compared illite and kaolinite clays as supplementary cementitious materials concluded that all of these kinds of materials have pozzolanic activity but differ in the temperature at which they activate [18]. It is important to note that in this study, it was possible that the illite had a disordered structure-a normal characteristic of this mineral [19]-and so activated with kaolinite in the same temperature range.…”
Section: Characterizationmentioning
confidence: 48%
“…On the other hand, when the correlations between SAI and the characterization variables were evaluated, it was found that the only characterization that had a relationship higher than 75% was kaolinite content. It is important to note, however, that although many researchers have studied the relationship between SAI and kaolinite [16,3,6,17], it was also relevant to the present study, although these kinds of materials showed low values of kaolinite and had a high quartz content, which could suggest that these kinds of materials' pozzolanic activity are related to the clay content more than the kaolinite content, which has been suggested by Msinjili et al, referring to the pozzolanic activity of illite clays [18].…”
Section: Characterizationmentioning
confidence: 61%
“…After pre-treatment at 120 • C, the kaolinite significantly decreased, and following calcination at 750 • C, none of these remained, as they were completely decomposed to the amorphous phase [52][53][54]. Illite was also not observed after calcination, and it is surmised that it was converted to muscovite during the calcination process due to dihydroxylation [55]. Muscovite is not observed in the natural clay or when only heated to 120 • C, but the quantity of illite reduced at 120 • C, with a small increase in rutile and chlorite observed together with that in quartz.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Also present were minor amounts of metakaolin (from the calcination of kaolinite), feldspar (mainly albite), illite, calcium carbonate (calcite) and calcined mica (mainly biotite and muscovite). The presence of metakaolin and partially calcined illitic clay indicated that the calcined soil would show pozzolanic activity (illites reach complete calcination at higher temperatures (~950 • C) [48]). The overall higher background of the calcined soil's XRD trace, most importantly between 15 and 30 2θ • , indicates a greater content of amorphous phases in the heat-treated soil compared with that of the concrete sand [49].…”
Section: Compositional Differencesmentioning
confidence: 99%